Socio-emotional competencies and their relationship with the perception of stress in students of the Escuela Normal Superior de México - Sánchez Serrano, Cinthia Jessica (2024)
The professions related to the care of users are those that manifest higher levels of stress historically, an element that increases when the attention is to more than one beneficiary at a time, one of these careers is teaching, because day by day teachers develop their work avoiding various social phenomena such as the different types of violence that are experienced inside the school, exclusion, varied family models, conflicts, lack of resources, inequality, to name a few. This outlines a scenario full of demands for the teacher which represents an emotional charge that promotes the suffering of stress. The purpose of this paper is to identify the stress coping mechanisms and socio-emotional competencies with which they are linked in a group of normal students, through a non-experimental cross-sectional-descriptive quantitative study, carried out in July 2020, with a sample of 226 students. To this end, two instruments were applied, one that measured the situations that arise in life and that are assessed as stressful, and as a second instrument, a socio-formative analytical rubric of socio-emotional competencies was applied, which includes inter- and intrapersonal competencies. Among the findings, students show a moderate level of stress, on socio-emotional competencies it was found that the areas of immediate attention are social awareness and empathy. Some of the conclusions are to emphasize the formation of socio-emotional competencies and their potentiation in the educational system, as well as the approach of not working separately.